HABITAT RUSA TIMOR (Cervus timorensis) DI DESA ATIAHU KECAMATAN. SIWALALAT, KABUPATEN. SERAM BAGIAN TIMUR - Intan. F Ninda Muar; C. K Pattinasarany; L. Latupapua (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2021)
The Habitat of the Timor Deer (Cervus timorensis) In Atiahu Village, Siwalalat District, East Seram Regency. This study aims to determine the habitat conditions of the Timor deer (Cervus timorensis) in Atiahu Village, Siwalalat District, East Seram Regency. This research was conducted using the description analysis method of the habitats found at each observation location, carried out through vegetation analysis, namely data collection which was carried out directly in the field, by observation. Observation, which is a data collection technique by observing things that are the target of research. Documentation, is a data collection technique by documenting data sources in the field related to the problem under study. The results of the study indicate that the forest in Atiahu Village has four types of habitats including, Lowland Forest, Grasslands, River Banks, and Coastal Forests